Archives and Special Collections at the University of La Verne: Putting the Repository of a Small Liberal Arts College to Work Online. Issue 1 (March 2018) - Jenkins, Benjamin; Darancette, Keren
Archives and Special Collections at the Wilson Library of the University of La Verne, located in inland southern California, offers an informative case study of descriptive practices and metadata attached to digital collections at a small liberal arts college. Since recruiting a staff specifically tasked to manage the archives, the Wilson Library has increased the number of collections available to patrons online through the creation of a digital collections Web page. Digitized, hosted collections include the papers of a faculty member from the early 20th century, photographs of early La Verne, historic local newspapers, and manuscript sources regarding Japanese American internment. Metadata fields at Wilson Library have developed to encompass a greater variety of contextual information about digitized records, improving users' ability to put the collections to use for research. Ultimately, this case study demonstrates what a library at a small university can accomplish with a dedicated staff and a clear objective, even with limited resources.